2007
DOI: 10.1002/crat.200610783
|View full text |Cite
|
Sign up to set email alerts
|

Influence of citric acid on calcium sulfate dihydrate crystallization in aqueous media

Abstract: The crystallization of Calcium sulfate dihydrate produced by the reaction between pure Ca(OH) 2 suspension and H 2 SO 4 solution was investigated at different pH values, temperatures and citric acid concentrations. Crystal size distributions, filtration rates and zeta potentials of gypsum were determined as a function of citric acid concentrations at pH 3.5 and 65°C. The influence of citric acid on the morphology of gypsum was also investigated and discussed. The average particle size of gypsum was reached to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 14 publications
2
32
0
2
Order By: Relevance
“…In our previous paper, we demonstrated the effect of citric acid on gypsum crystallization in aqueous media at different pH values, temperatures, and citric acid concentrations [12]. In this study, we found that the pH did not affect the average particle size but it had a great effect on the gypsum shape at 20°C.…”
Section: Introductionmentioning
confidence: 56%
“…In our previous paper, we demonstrated the effect of citric acid on gypsum crystallization in aqueous media at different pH values, temperatures, and citric acid concentrations [12]. In this study, we found that the pH did not affect the average particle size but it had a great effect on the gypsum shape at 20°C.…”
Section: Introductionmentioning
confidence: 56%
“…The laboratory filtration data were used to calculate the cake parameters based on Darcy's law [13]. The inverse of time rate change of the filtrate volume during filtration is expressed as: A plot of dh/dV as the dependent variable and V as the independent variable results in a straight line where K p and B are the slope and intercept, respectively.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…In this study, we found that pH does not affect the average particle size but it has great effect on the shape of gypsum at 20°C. It was also deduced that citric acid plays an important role for gypsum morphology (size and shape) at pH 3.5 and 65°C and approximately 2500 ppm citric acid concentration was determined as an optimum concentration in terms of average crystal size, crystal shape, and filtration characteristics [8].…”
Section: Introductionmentioning
confidence: 99%
“…The laboratory filtration data were used to calculate the cake parameters based on Darcy's law [15]. Details of this method were presented in our previous paper [8].…”
Section: Introductionmentioning
confidence: 99%